(untitled) (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2025)
Calliandra haematocephala belongs to Fabaceae, is an ornamental shrub.It is native to Bolivia, but widely cultivated in India.It is traditionally used for treating infections, inflammation, neurological disorders and metabolic diseases.Phytochemical survey revealed the presence of flavanoids, terpenoids, saponins, phenolic compounds, glycosides, and alkaloids. These compounds exhibit a wide range of pharmacological activities such as antimicrobial, antioxidant, anti-inflammatory, neuroprotective, antidiabetic, anticancer, and hepatoprotective effects. Leaves were collected, washed with water, shade dried, powdered and extracted with 70% hydroalcohol. The extract was concentrated and stored in air tight container for further use. This study aims to identify the bioactive constituents present in the hydroalcoholic extract of Calliandra haematocephala (HAECHL) using Gas Chromatography–Mass Spectrometry (GC-MS). GC-MS chromatogram showed phytoconstituents which may attribute to eighteen phytoconstituents, which may contribute to the plant’s diverse pharmacological activities such as, treating infections, pain, inflammatory and neurological disorders.